CaM promotes cardiomyocyte mitophagy in myocardial ischemia-reperfusion injury involving in the regulation of the IP3R3-GRP75-VDAC1 complex - Bi-Ying Liu; Zhao-Hui Dai; Li Mao; Ling-Zhi Guo; Zhong-Bao Yang (Scientific Reports)
Abstract The pathogenesis of myocardial ischemia-reperfusion injury (MIRI) is not fully clear. This study aims to investigate the role of mitochondrial-associated endoplasmic reticulum membrane (MAM)-related calcium overload in mitophagy. In vitro and in vivo models were established to simulate MIRI. Cellular injury, apoptosis and mitophagy were measured and gene expression was analysized. The expression levels of glucose-regulated protein 75 (GRP75), receptor for inositol 1,4,5-trisphosphate (IP3R3), voltage-dependent anion-selective channel 1 (VDAC1), and calmodulin (CaM) and the mitochondrial calcium content, mitophagy and apoptosis were significantly increased in MIRI or hypoxia/reoxygenation (H/R) cells when compared to controls, but the mitochondrial membrane potential and ATP significantly decreased. GRP75 knockdown significantly inhibited CaM expression, mitochondrial calcium overload and mitophagy of H9C2 cells, whereas had no significant effect on IP3R3 and VDAC1 expression. CaM knockdown had no significant effect on the expression of GRP75, IP3R3 and VDAC1, and on mitochondrial calcium concentration, ATP levels and mitochondrial membrane potential of H9C2 cells, but significantly inhibited mitophagy and apoptosis. Collectively, these data suggest that the IP3R3-GRP75-VDAC1/CaM axis plays an important role in mitochondrial autophagy injury during myocardial ischemia-reperfusion and that it is a potential target for MIRI treatment.